Salt stress and K/Ca ratios of the nutrient solution in the production and quality of the melon - Ramayane Torquato Oliveira, Renata; de Assis de Oliveira, Francisco; Maria de Morais Neta Góis, Helena; Victor de Menezes, Paulo; Thomaz dos Santos, Sandy; Maria Mendes Aroucha, Edna; Gustavo Lima de Almeida, José (Revista Ciência Agronômica, 2023)
Melon cultivation under saline conditions is a challenge, as the plants can suffer a reduction in fruit production and quality. The aim of this study was to evaluate the production and quality of noble melon fruit fertigated with different saline solutions and K/Ca ratios. The experimental design was of randomised blocks, with treatments arranged in a 3 x 6 factorial scheme, using three melon cultivars (Bazuca, McLaren, County) fertigated with six nutrient solutions [S1 – standard nutrient solution (SNS); S2 – SNS + NaCl (5.0 dS m-1); S3 – S2 enriched with K (50%); S4 – S2 enriched with K (100%); S5 – S2 enriched with Ca (50%); S6 – S2 enriched with Ca (100%)]. At the end of each cultivar cycle, the fruit was harvested and assessed for the following parameters: fresh fruit weight, fruit diameter, internal cavity, pulp thickness, pulp firmness, soluble solids content, titratable acidity, soluble solids/titratable acidity ratio, and vitamin C. Salt stress impaired the physical characteristics of the fruit of the three noble melon cultivars. The nutrient solution enriched with 50% K (S3) did not reduce the effect of salt stress on fresh weight or fruit size in the melon, but afforded an increase in fruit quality.